Physicochemical & Microbial Characterization of Overripe Tempeh - Djunaidi, Stefani; Tirtaningtyas Gunawan-Puteri, Maria Dewi Puspitasari; Wijaya, Christofora Hanny; Prabawati, Elisabeth Kartika (International Series on Interdisciplinary Science and Technology, 2017)
Abstract— Recent research showed potencies of overripe tempeh for development as condiment, and therefore, requirement of guiding parameters related to sensory properties. In this study, four samples of overripe tempeh from single source of soybean with different processing method were observed. All samples were characterized with comparable brown color (L* 52.96, a* 6.84, and b* 18.52), and total number of lactic acid bacteria (8.30 – 8.46 log CFU/g). All samples also have similar trends of protein and soluble amino acid content (50.32 – 61.77 mg BSA eq/g dry base, 357.39 – 418.78 mg tyrosine eq/g dry base) compared to fresh tempeh (62.43 mg BSA eq/g dry base, 71.70 mg tyrosine eq/g dry base). The findings indicated suitability of above parameters as guidance in target overripe tempeh for condiment ingredients. Observation of total microbial and total yeast and mould showed that these parameters were affected with production method of overripe tempeh. Keywords— Overripe tempeh, guiding parameters, microbial characterization, physicochemical characterization